Textile Antenna Integrated with Compact AMC and Parasitic Elements for WLAN/WBAN Applications - Herwansyah, Lago; Ping, Jack Soh; Mohd Faizal, Jamlos; Nursuriati, Shohaimi; Sen, Yan; Vandenbosch, Guy A. E. (Springer Berlin Heidelberg, 2016)
A wearable antenna fully designed and fabricated using textile is presented. Both antenna and artificial magnetic conductor plane are designed for operation in the wireless local area network (WLAN)/wireless body area network (WBAN) band from 2.4 to 2.5 GHz. The AMC unit element is designed based on the rectangular patch structure, which is then integrated using slots and slits for bandwidth broadening. Meanwhile, the combination of the slits and L-shaped parasitic elements applied at four edges of the rectangular antenna structure enabled unidirectional radiation outwards from the body. The structure is coaxially fed using a rectangular ring slot centered on the radiating element. Simulated and measured reflection and radiation performance indicate a satisfactory agreement, fulfilling the requirements for WLAN/WBAN applications both in free space and on body. The shielding effectiveness provided by the AMC plane is also evaluated numerically in terms of specific absorption rate, indicating levels below the European regulatory limit of 2 W/kg.